DEIXIS ANALYSIS OF THE SONG LYRICS SHAPE OF YOU BY ED SHEERAN - Fattaakhul Ilma; Yuliyanto Sabat (IKIP Siliwangi, 2023)
This study intended to analyze the deixis category, the dominance of deixis usage and analyzed reference meaning from deixis which was used in a song lyrics of Shape of You by Ed Sheeran. The research question of this research were as follows: the kinds of deixis were employed in this song lyrics, the most frequently types of deixis were applicated in this song lyrics, and the reference meaning related of the deixis used in this song lyrics. This research used the deixis theory from George Yule. The researcher used descriptive qualitative method. The song lyrics Shape of You by Ed Sheeran were the data of this research. The data were collected by listening, reading the script of the song lyrics, and taking notes of the song lyrics Shape of You’s by Ed Sheeran. The results of the study shows that the type of deixis used in the song's lyrics were deixis of person, temporal, and spatial. Person deixis was dominant in this research which consisted of 23 or 64% deixis. The reference meaning of this research refers to the author, mentioning location or relative position in the song, and the time of the story in the song. Keywords: Pragmatics; Deixis; Song Lyrics